Answer:
cost = 8p + 5
Step-by-step explanation:
$8*[number of pizzas] + $5 delivery fee
$8p + $5
8p + 5
cost = 8p + 5
Answer
• A. Equation: 25(5 + x) = 325
,
• B. Answer: 8 dogs
Explanation
Given
• Charge to wash a dog: $25.
• She washed 5 dogs on Saturday and then some more on Sunday.
• She made $325 for the weekend.
Procedure
She charges $25 per wash, she made $325 for the weekend, and we know that on Saturday she washed 5 dogs, but we don't know how many she washed on Sunday. Thus, we have to build an equation in which the number of dogs washed on Sunday is represented by x (as we do not know the real number).
Considering that the total money made has to be equal to the multiplication of the charge times the dogs washed, the equation is:
![25(5+x)=325](https://tex.z-dn.net/?f=25%285%2Bx%29%3D325)
Then, we have to solve for x to know how many dogs did she wash on Sunday.
0. Multiplying the parenthesis
![125+25x=325](https://tex.z-dn.net/?f=125%2B25x%3D325)
<em>2. Subtracting 125 from both sides of the equation</em>
![125-125+25x=325-125](https://tex.z-dn.net/?f=125-125%2B25x%3D325-125)
![25x=200](https://tex.z-dn.net/?f=25x%3D200)
<em>3. Dividing both sides of the equation against 25</em>
![\frac{25x}{25}=\frac{200}{25}](https://tex.z-dn.net/?f=%5Cfrac%7B25x%7D%7B25%7D%3D%5Cfrac%7B200%7D%7B25%7D)
We know that
if <span>(ax + b)(cx - d) = 0
then
</span><span>(ax + b)= 0-----> ax=-b------> x=-b/a
and
</span><span>(cx - d) = 0-----> cx=d------> x=d/c
therefore
the answer is the option
</span><span>C. -\frac{b}{a}</span>
Given:
First side(A): 2B - 7
Second side(B): B
Third side(C): B + 4
Plug in values:
A + B + C = 80
2B - 7 + B + B + 4 = 80
If you look at the coefficients only, you can rewrite the equation like this:
2B + B + B - 7 + 4 = 80
This means that 4B - 7 + 4 = 80
=4B - 3 = 80
= 4B = 80 + 3
B = 83/4, so you can either write B as 83/4 or as 20.75.
Checking your work:
A: 2(20.75) - 7 = 34.5
B: 20.75
C: 4 + 20.75 = 24.75
34.5 + 20.75 + 24.75 = 80cm.
Hope this helped.
Answer:
-36
Step-by-step explanation:
Just plug in -12 for x
f(x) = 4 x (-12) -12
-48 - 12 = -36